Aktivitas Masyarakat Industri terhadap Lingkungan Ditinjau Berdasarkan Perspektif Konflik - Deni Kurniawan (Talenta Publisher, 2024)
Industrial activities often cause significant environmental damage. This paper analyzes the root causes from a conflict perspective and identifies solutions that can address these issues. By understanding the dynamics of conflict between industry and the environment, we can design more effective policies and strategies to achieve sustainable development. Keywords: Industry, conflict, environment.